Efficacy of screening women at high risk of hereditary ovarian cancer: results of an 11-year cohort study. (1st January 2006) - Gaarenstroom, K. N.; Van Der Hiel, B.; Tollenaar, R. A.E.M.; Vink, G. R.; Jansen, F. W.; Van Asperen, C. J.; Kenter, G. G.
Abstract : The outcome of screening and prophylactic surgery in 269 women at high risk of hereditary ovarian cancer is reported. Screening was performed using transvaginal ultrasound and serum CA125 testing. Mean follow-up was 26 months (583 person-years). A total of 113 (42%) of 269 women had a pathogenic BRCA1 or BRCA2 mutation, and 127 (47%) of 269 women underwent salpingo-oophorectomy. No occult cancers were found. In eight women having both elevated CA125 levels and abnormal ultrasound findings, a malignancy was found. Four of these cancers (one borderline, one stage Ia, one stage IIIb, and one stage IIIc ovarian or peritoneal cancer) were detected at the first screening visit. One stage IIIb and one stage IIIc cancer were detected at the second screening visit after 12 months, and two interval stage IIIc and IV cancers were detected 8 and 10 months after the first screening visit. No peritoneal carcinoma was found among those 114 women who underwent bilateral salpingo-oophorectomy with normal or benign pathology results, after a mean follow-up of 16 months (152 person-years). We conclude that the efficacy of screening women at high risk of ovarian cancer seems poor because the majority of cancers were detected at an advanced stage.